Cultural Extension of Taxodium in the Territory of Slovakia and Its Genetic-Genomical Notes - Mňahončáková, Erika; Ražná, Katarína; Hrubík, Pavel (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The subject of the research was to find out the cultural expansion of two species of Taxodium, namely Taxodium ascendens (Brongn.) and Taxodium distichum (L.) L. C. Rich. The occurrence of individuals was recorded on 18 different localities of Slovakia, obtaining the taxonomic-dendrometric characteristics of individual trees. Appropriate methodologies and available devices have been used. Biological data, such as tree planting, health status, landscaping value, and tree age were recorded. The Taxodium distichum (L.) L. C. Rich. is found in 15 localities in Slovakia and in the three localities of Taxodium ascendens (Brongn.). Regarding the number of trees represented, Taxodium distichum contains 35 trees growing on individual localities, of which 3 are state-protected trees. We did not confirm 9 trees at registered locations. In general, we have seen a declining level of maintenance and care for our historic parks and state-protected trees. Literary records characterizing the genome of these rare species are focused on the study of genetic variability and polymorphism mapping using various types of molecular markers to elucidate the genetic essence of phenotypic variability and the historical structure of species populations.